2021
DOI: 10.1101/2021.03.17.21253131
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interim results of the safety and immune-efficacy of 1 versus 2 doses of COVID-19 vaccine BNT162b2 for cancer patients in the context of the UK vaccine priority guidelines

Abstract: Background: The efficacy and safety profile of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have not been definitively established in immunocompromised patient populations. Patients with a known cancer diagnosis were hitherto excluded from trials of the vaccines currently in clinical use. Methods: This study presents data on the safety and immune efficacy of the BNT162b.2 (Pfizer-BioNTech) vaccine in 54 healthy controls and 151 mostly elderly patients with solid and haematologi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 30 publications
6
67
0
3
Order By: Relevance
“…Antibody testing post-vaccination may also play other roles. It may be useful to identify individuals in high risk groups who do not seroconvert 19 , who may remain at higher risk of infection, and may benefit from tailored advice around social contact, and, depending on underlying comorbidity, from further vaccination doses e.g. if immune reconstitution is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody testing post-vaccination may also play other roles. It may be useful to identify individuals in high risk groups who do not seroconvert 19 , who may remain at higher risk of infection, and may benefit from tailored advice around social contact, and, depending on underlying comorbidity, from further vaccination doses e.g. if immune reconstitution is expected.…”
Section: Discussionmentioning
confidence: 99%
“…Polack et al investigated the safety and e cacy of the BNT162b2 mRNA Covid-19 vaccine in healthy adults or those with chronic stable medical conditions, excluding patients treated with immunosuppressive therapies or diagnosed with immunocompromising conditions [1]. It was later observed that in immunocompromised patients, the elicited immune response to mRNA Covid-19 vaccine is reduced [2][3]. Boyarsky et al showed the poor humoral response elicited in a study of 346 solid organ transplant recipients [2].…”
Section: Introductionmentioning
confidence: 99%
“…Boyarsky et al showed the poor humoral response elicited in a study of 346 solid organ transplant recipients [2]. Monin-Aldama et al showed that the post-BNT162b2 immune e cacy was strikingly low in solid cancer patients and even lower in patients with hematologic malignancy [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, 2021; the CDC began permitting a delay of up to 6 weeks for second doses of mRNA vaccines on Jan. 21, 2021. One caveat to this approach is that data around the durability of first-dose protection are lacking for some subgroups, such as older adults, people who are immunocompromised or patients with cancer, 27 given concerns that prolonged viral replication in immunocompromised hosts may promote the emergence of more SARS-CoV-2 variants. 28 Our analysis not only informs Canadians wondering how many others are in the same risk stratum as they, but also serves to emphasize the importance of continuing to follow public health advice such as universal masking, physical distancing and frequent hand washing as vaccination programs proceed, given that most adults in Canada have at least 1 risk factor for severe COVID-19.…”
Section: How Should Canada's Rollout Of Sars-cov-2 Vaccinations Proceed?mentioning
confidence: 99%